Evidence on the Validity of Management Education - Luthans, Fred; Walker, James W.; Hodgetts, Richard M. (Academy of Management Journal, 1969)
The authors feel that more attention should be given to the empirical validation of management education. In order to determine what effect a college degree and the academic major have on promotability, 3,202 marketing personnel of a major petroleum corporation were analyzed.